Managing sustainable development by human capital reproduction in the system of company's organizational behavior - Arefieva, O; Polous, O; Arefiev, S; Tytykalo, V; Kwilinski, A (IOP conference series. Earth and environmental science, 2021)
In the framework of this study, the essential features of the systematic approach application in the process of managing sustainable development by company's human capital reproduction and intellectualization were identified. The characteristics of the system that are able to ensure its integrity, continuity of operation, adaptability and ability to self-study, self-organization are highlighted. The successive stages of individual human capital reproduction in the process of its circulation are determined. The key stages of company's human capital reproduction with taking into account the factors of internal and external environment are singled out. Production volumes for industrial enterprises of Ukraine using the Cobb-Douglas function are predicted. Levels of company's organizational behavior for the purpose of defining features of company's human capital reproduction on each of them are allocated. The mechanism for managing sustainable development by human capital reproduction in the system of company's organizational behavior is offered. A set of measures aimed at effective implementation of the proposed mechanism and intensification of the company through its human capital reproduction in the system of organizational behavior are developed.